Residents’ Emotional State and Attitude Towards Tourists: A Psychological Perspective from Kwahu Traditional Area of Ghana (Ghana Journal of Science, Technology and Development, 2025)
As an important component of destination experience, residents’ emotional experience plays an important role in destination marketing. This study examines residents’ emotional experiences about tourists using discrete emotions (happy, anger, guilt, sadness, fear and surprise). The study area is Kwahu Traditional Area characterised by exponential increase in tourist arrivals as a result of varied tourists’ attractions and events. Emotions were measured retrospectively using self-report. Participants rated their own emotions on the Differential Emotional Scale, before indicating their final judgment. In addition, Positive and Negative Affect Schedule was used to classify these emotional states into Positive Affect and Negative Affect using a concurrent mixed-method involving 569 survey respondents and 15 in-depth interviews, the study found that even though some residents appear to have mixed emotional experiences toward tourists, more than half of residents reported strong positive emotional state toward tourists as against negative emotional state. The study discovered that, positive emotions such as joy, happiness, honoured, pleasure, cheerful, inspire, satisfy and positive surprise were strongly experienced. The results further shows that residents generally demonstrate positive emotional states towards tourists across socio-demographic characteristics such as age, education attainment, religion, marital status and community of residence. The study contributes to tourism management literature by explaining how residents' emotional states can be utilized to market tourists’ destination areas and also provides evidence for planning and sustainable tourism development.